Associative Agreement as a Predictor of Naming Ability in Alzheimer's Disease: A Case for the Semantic Nature of Associative Links - Zannino, Gian Daniele; Perri, Roberta; Teghil, Alice; Caltagirone, Carlo; Carlesimo, Giovanni A. (Frontiers in Behavioral Neuroscience, 2018)
We aimed to address the long-standing issue of the nature of the relationships that link a cue word to words associated with it. In keeping with a recently proposed neuropsychological model of semantic memory (Zannino et al., 2015), we provide support for the hypothesis that associative links are semantic in nature and not lexical. In support of this hypothesis, we demonstrate a relationship in healthy subjects between the probability of producing word X in response to cue word Y in a free association task and the probability of using word X to describe the meaning of word Y. Furthermore, we provide evidence that associative measures are altered in people suffering from Alzheimer’s disease (AD) and predict their level of performance in a picture-naming task. We provide a parsimonious account of the experimental data gathered form these different sources of evidence according to the hypothesis that the links between a cue word and its associates can be viewed as binding a concept (the cue) to pieces of information regarding its meaning (the associates).